Ecological correlates of taxonomic and functional beta diversity of wetland breeding birds in central part of Inner Mongolia wetlands - Ling-Ying Shuai; Yu-Xin Luo; Yue Luo; Jing-Wen Bai; Di Meng; Fu-Jia Sha; Ke Shi; Wan-Lan Ma; Fu-Shun Zhang (Ecological Indicators)
Wetlands in Inner Mongolia provide necessary habitats for many bird species and are considered important for biodiversity conservation. However, studies on spatial variation of bird communities within this region remain limited. In this study, we conducted a large-scale investigation on breeding birds in 30 lakes located in the central part of Inner Mongolia. We explored the ecological correlates of taxonomic and functional beta diversity among avian communities using Mantel tests. Both taxonomic and functional beta diversity were partitioned using two approaches, namely a species turnover component versus a nestedness-resultant component, and local contributions versus species contributions to the overall variation in species composition. A total of 105 breeding bird species were recorded, with 5 species considered threatened by IUCN Redlist. Although we detected a significant association between taxonomic and functional beta diversity, they differed greatly in terms of composition and ecological correlates. Taxonomic beta diversity was dominated by its turnover component, whereas functional beta diversity was dominated by its nestedness-resultant component. We found a positive relationship between dissimilarity in temperature and taxonomic beta diversity, and a positive relationship between difference in lake area and taxonomic nestedness-resultant component. No significant association was found between the environmental variables and functional beta diversity. We also detected several lakes and species that contributed most to the overall beta diversity. Species-poor lakes tended to contribute more to the overall beta diversity. While large lakes with high richness are normally considered important, our results highlighted the importance of protecting small, species-poor lakes with high ecological uniqueness.